PENGARUH LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN HOTEL THE HAVEN SUITES BALI BERAWA - Kadek Dirda Dwiadnyani; Ni Wayan Mekarini (Universitas Triatma Mulya, 2022)
The research aims to see the effect partially and simultaneously between the work environment and work stress on employee performance, as well as to see the effect of independent variables simultaneously on the dependent variable. The respondents of this study were all employees. The results of the analysis questionnaire included descriptive statistical analysis test, validity and reliability test, classical assumption test, multiple regression analysis, t test and f test. As well as analysis of the coefficient of determination The results show that the results of the regression analysis that partially the Work Environment has a positive and significant effect on the Performance of Employees of The Haven Suites Bali Berawa Hotel and Job Stress has a positive and significant effect on Employee Performance of The Haven Suites Bali Berawa Hotels. Simultaneously the Work Environment and Work Stress have a positive and significant effect simultaneously on Employee Performance at The Haven Suites Bali Berawa. The amount of influence contributed by the work environment and stress to employee performance is 31.9% while the rest is determined by other factors which are not discussed and researched. in research